Do managers disclose more risks when given a chance to explain? The effects of risk disclosure regimes on managers’ risk disclosure choices - Feng, Yeo (2016)
I conduct two experiments to examine managers’ risk disclosure decisions across two regimes. The first regime is based on the current U.S. Form 10-K risk factors disclosure setting, where risks are to be disclosed on a standalone basis with no risk mitigation information allowed. Managers under this first regime are thus not allowed to simultaneously explain how each risk is handled by their firm. The second regime is modeled after German risk reporting standards, where risk mitigation information is to be simultaneously disclosed alongside each risk. Using a measure that captures participants’ disclosure volume and specificity, I experimentally test how participants’ risk disclosure levels vary across these two regimes. Unlike an archival setting where only the final disclosure outcomes can be observed, an experimental setting allows me to hold constant the full set of firm risks known to managers, and observe both disclosed and undisclosed risks under each regime. My 2 × 2 × 2 mixed factorial experiment varies the risk disclosure regime (mitigation or no-mitigation) and managers’ reporting goal (strategic or transparent) between-subjects, and risk mitigation strength (weak or strong) within-subjects. I predict and find that participants with a transparent reporting goal disclosed both weakly and strongly-mitigated risks at similar levels across both regimes. However, contrary to concerns that a mitigation regime leads to reduced disclosure of weakly-mitigated risks, I find no difference in the disclosure level of weakly-mitigated risks by strategic participants across both regimes. Instead, strategic participants only disclosed more strongly-mitigated risks under a mitigation regime, relative to a no-mitigation regime. Strategic participants in a mitigation regime were also more willing to elaborate upon, and provide non-boilerplate disclosures for both weakly and strongly-mitigated risks. In addition, I document evidence consistent with strategic disclosure behavior for these strategic participants. Under a mitigation regime where investors and regulators could readily infer how well each risk was handled, strategic participants disclosed the same number of weakly and strongly-mitigated risks to avoid sending signals of over or under-disclosure. However, under a no-mitigation regime, strategic managers disclosed more weakly than strongly-mitigated risks. My results suggest that there may be practical benefits to allowing the simultaneous disclosure of risk mitigation plans alongside risk disclosures, and sheds light on the differences in disclosed risk mix under each regime.